Promoting Sustainable and Intelligent Freight Transportation Systems in the Barcelona Metropolitan Area - Calvet, Laura; Alvarez-Palau, Eduard J.; Viu, Marta; Castillo, Cristian; Copado, Pedro; Juan, Angel A. (Transportation research procedia (Online), 2021)
The growth of e-commerce and the on-demand economy in urban and metropolitan areas has been accelerated by the recent COVID-19 pandemic. As a consequence, logistics and transportation operators are subject to a noticeable pressure to develop efficient delivery systems. These systems are also influenced by the global trend towards more sustainable transportation and mobility, which implies changes in urban policies and technological innovations –e.g., the substitution of traditional diesel petrol-drive vehicles by electric ones. This paper analyzes the current and predicted needs of logistics operators in the Barcelona metropolitan area. To do so, urban regulations are analyzed and key shareholders are interviewed. The analysis of these interviews promote a discussion on how the use of new ‘agile’ optimization algorithms –which are based on the combination of biased-randomized heuristics, computer parallelization techniques, and IoT / 5G technologies– can contribute to enhance urban distribution practices. Finally, we present a case study in which the effect of different configurations of working/resting times and parking areas availability on routing solutions is studied. Our research aims to provide comprehensive knowledge to managers and policy-makers, and to offer them with powerful tools capable of generating real-time solutions to complex last-mile delivery challenges under dynamic conditions.